Pemberdayaan Pembudidaya Ikan Melalui Progam “Peti Koin Bermantra” untuk Meningkatkan Ekonomi Masyarakat: Studi Di Desa Dawuhan Kabupaten Malang - Dewi Yasmine Ammaratih; Anggraeny Puspaningtyas; Eddy Wahyudi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The main problem in empowering fish farming communities in Dawuhan Village, Poncokusumo District, Malang Regency is how to empower communities through the Peti Koin Bermantra Program in Dawuhan Village, Malang Regency, such as low managerial capacity, weather constraints, high feed prices, and limited market access, which have an impact on the suboptimal economic improvement of the community. This study aims to analyze the implementation of the Peti Koin Bermantra Program in empowering fish farming communities to improve their economic welfare. The study uses a qualitative method with a descriptive approach, as well as the community empowerment theory of Hashemi, Schuler, and Riley (1996). The results show that the Peti Koin Bermantra Program contributes positively to improving community welfare through eight empowerment indicators, such as increased mobility, small-scale purchasing power, ability to make larger purchases, involvement in major decisions, freedom, political and legal awareness, participation in public protests and political campaigns, economic security, and contribution to family support. The success of the program was supported by collaboration between facilitators, the East Java Provincial Marine and Fisheries Service, and the Malang Regency Fisheries Service, although there were still obstacles in terms of capital, group management, and product innovation. To support the sustainability of the program,